Primary aldosteronism patients with previous cardiovascular and cerebrovascular events have high aldosterone responsiveness to ACTH stimulation - Eriko Nakano; Kosuke Mukai; Atsunori Fukuhara; Michio Otsuki; Iichiro Shimomura; Takamasa Ichijo; Mika Tsuiki; Norio Wada; Takashi Yoneda; Yoshiyu Takeda; Kenji Oki; Tetsuya Yamada; et al. (Endocrine Journal)
Aldosterone secretion in primary aldosteronism (PA) is often regulated by adrenocorticotropic hormone (ACTH) in addition to its autonomous secretion. However, the clinical characteristics and risk of cardiovascular and cerebrovascular (CCV) events in PA patients with aldosterone responsiveness to ACTH stimulation remain unclear. This study aimed to investigate the prevalence of CCV events in PA patients with high aldosterone responsiveness to ACTH stimulation. A retrospective cross-sectional study was conducted as part of the Japan Primary Aldosteronism Study/Japan Rare Intractable Adrenal Disease project. PA patients with adrenal venous sampling (AVS) between January 2006 and March 2019 were enrolled. The ACTH-stimulated plasma aldosterone concentration (PAC) of the inferior vena cava during AVS was used to evaluate aldosterone responsiveness to ACTH. We analyzed the relationship between responsiveness and previous CCV events. Logistic regression analysis demonstrated that the ΔPAC (the difference between the PAC measurements before and after ACTH stimulation) significantly increased the odds of previous CCV events in PA patients after adjusting for classical CCV event risk factors, baseline PAC and duration of hypertension (relative PAC: odds ratio [OR], 2.896; 95% confidence interval [CI], 0.989–8.482; ΔPAC: OR, 2.344; 95% CI, 1.149–4.780; ACTH-stimulated PAC: OR, 2.098; 95% CI, 0.694–6.339). This study clearly demonstrated that aldosterone responsiveness to ACTH is closely related to previous CCV events. The responsiveness of the PAC to ACTH could be useful in predicting CCV event risk. Registration Number in UMIN-CTR is UMIN000032525.